Searching for Ultra-compact binary stars with the MeerLICHT Southern All-Sky Survey - Lees, Robert (Department of Astronomy, 2023)
An effort was made to expand the known population of AM Canum Venaticorum (AM CVn) stars, a rare type of ultra-compact binary star. This was done by searching through the MeerLICHT Southern All-Sky Survey (ML SASS) data with a candidate selection process which made use of a selection technique based on the colours of stars. The candidates found were then observed with an extensive follow-up observation campaign which included both high-speed photometric observations and longslit spectroscopy. Over 20 weeks of observing were conducted, I conducted 9 of them myself and the rest were handled by other members of the MeerLICHT working group. These observations were conducted with multiple telescopes at the South African Astronomical Observatory (SAAO) in Sutherland. Over 100 targets were observed photometrically and over 150 spectra were obtained, out of a possible 251 primary candidates. The photometric lightcurves were then analysed by producing Lomb-Scargle periodograms for each of the observed target lightcurves searching for variability on the order of 5 to 65 minutes. All of the observed spectra were processed and searched for certain hydrogen, helium and metal absorption and emission lines. Unfortunately, no new AM CVns were found, although a new potential magnetic cataclysmic variable (CV) was discovered and one unknown but highly interesting spectrum was discovered. The lack of AM CVns was not unexpected as these binary stars are exceptionally rare with a little over 70 currently known AM CVns in the entire sky, and our statistical analysis predicted that we would have only detected approximately one AM CVn this far into the follow-up campaign. Potential further work and methods to improve both the candidate selection process and the follow-up campaign are outlined.